Development of flourishing scale among a sample of Umm Al-Qura university students - Al-Sharif, Walaa Mansour; Sharaf, Sumaya Ezzat (Journal of Educational and Psychological Sciences, 2023)
The aim of this study is to constructing a flourishing scale, verify its validity and reliability, find out its factor structure that corresponds to the sample, and finally to examine the equivalence of the factor structure and the differences in the underlying average of the Flourishing Scale among Um Al-Qura University students, The study sample consisted of 422 students from Um Al-Qura University, and to achieve the study objectives a descriptive method was used and a study tool - prepared by the researcher – was applied including the flourishing scale of 40 items distributed over five dimensions (positive feelings, integration, relationships, meaning and achievement). The results of the factor analysis resulted in the deletion of 11 items with a saturation of less than 0.40, thus the scale consists of 29 items distributed over five dimensions (positive orientation towards life, self-achievement, social compatibility, spiritual affiliation and psychological compatibility). The results indicated a high degree of reliability and validity of the scale, and a high level of psychological flourishing among Um Al-Qura University students, and the results showed no statistically significant differences between males and females in the level of psychological flourishing, and indicated equal measurement of all items of the Flourishing Scale between males and females. Based on these results, the study recommended the preparation of training and educational programs to educate students about the importance of psychological flourishing, to expand the use of the scale which is distinguished with short and easy phrases, and to benefit from the scale in knowing the level of psychological flourishing among students of Saudi universities.